(untitled) (Revista Brasileira Multidisciplinar, 2024)
Beekeeping consists of the commercial exploitation of bees for the production of honey, pollen, royal jelly and propolis. It is developed in different regions of the federation, and has significant social, economic and environmental relevance. In this sense, the objective of this article was to carry out a systematic literature review on the subject in the Web of Science database, from 2018 to 2022, using the method recommended by Cronin, Ryan and Coughlan (2008). By defining the terms of inclusion and exclusion, 27 works related to the subject matter of study were selected. Furthermore, the Bibliometrix was used for graphic analysis and correlation of the works. There was a certain lack of work that addressed the management of the activity, marketing channels, qualitative attributes of beekeeping products, existing and emerging markets, among other factors that equally influence the degree of attractiveness in entering and remaining in the beekeeping activity.